Prioritas Pengembangan Beras Analog di Kabupaten Kupang Nusa Tenggara Timur - Aplonia Bani; Arista Marlince Tamonob; Delila Seran Nahak (Universitas Galuh, 2026)
Public dependence on rice as a staple food remains high, while local food diversification has not yet been optimally developed. This study aims to analyze the variables influencing consumer acceptance of three types of analog rice—corn, cassava, and porang—and to determine their development priorities. An organoleptic test was conducted using untrained panelists (students in Kupang Regency, n=16), employing a binary preference scale (like=1, dislike=0) for the variables of color, aroma, taste, texture, shape, and price. The data were analyzed using Penalized Logistic Regression (Odds Ratio/OR) to identify factors influencing consumer preference, and the Analytic Hierarchy Process (AHP) to determine product development priorities, with the assistance of R software version 4.5.1. The results show that for cassava-based analog rice, aroma was the dominant factor, with the highest odds ratio (OR=30.494). In addition, color, taste, texture, and price increased the likelihood of acceptance (OR>1), whereas shape reduced acceptance probability (O0.268). For corn-based analog rice, shape was the main determinant (25.633), followed by price (6.144), aroma, taste, and texture. In contrast, for porang-based analog rice, color and shape had the strongest influence on acceptance (12.60), while price reduced the likelihood of consumer acceptance (0.78). The AHP analysis identified cassava-based analog rice as the top development priority (42.33%), due to its lower price, preferred taste and texture, and attractive color. This was followed by corn-based analog rice (30.70%) and porang-based analog rice (26.98%).